Pengembangan sistem posyandu untuk pengelompokan gizi pada anak menggunakan metode prototype - Alam Supriyatna; Muhamad Haerul Saleh (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2019)
Flamboyan Posyandu is a place that makes it easy for parents to check their toddlers, toddlers, and children underneath in a stable condition or not early on. In the Posyandu, Flamboyan still does not have a nutritional grouping for children, due to the difficulty in grouping children's nutrition which requires facilities that are now available at the Posyandu. With the development of the Posyandu system to classify children based on nutrition using the Prototype method, the grouping that did not yet exist and was difficult could be carried out. The development of the Posyandu system has obtained the feasibility value obtained from 4 respondents, the value obtained is 86.96% which means the development of the Posyandu system is very feasible to use.